Do new entrants sustain, destroy, or create guaranteed profitability?. (5th March 2018) - MacDonald, Glenn; Ryall, Michael
Abstract : Research and Managerial Summary : We examine the effect of any new agent on the value captured by an incumbent: e.g., a new rival, a new source of supply, a new customer, etc. Regardless of the new agent's type, entry has two opposing effects on the incumbent's minimum profitability guaranteed by competition. First, is the creation of more economic value. This tends to blunt competition and lowers minimum guaranteed profit. Second, is the potential generation of new productive alternatives for the incumbent, thereby inducing the opposite effect. We describe whether entry allows guaranteed profits to persist or creates guaranteed profits when they did not previously exist. We show that knowing that the entrant can replace the incumbent is not enough to determine the impact of entry on guaranteed minimum profits.